Study of system earthing for 36 kVcollector grids for wind farms - Jansson, David; Wadström, Patrik (My University, 2014)
For wind farms, it has become more common to use system voltage of 36 kV for the collector grids. However, in Sweden there are guidelines and standards for voltages up to 24 kV but low voltages result in higher losses. For power systems with voltage levels above 24 kV, clear instructions for how to perform system earthing are lacking; this means that many opportunities are allowed for 36 kV collector grids. The purpose of this study is to identify different alternatives of how to system earth a wind farm with system voltage of 36 kV. This thesis consists of two major parts; a mapping of present solutions and a simulation part. By contacting different developers and owners of wind farms, their method for system earthing may be identified. Wind farms that are selected for the mapping consists of at least 10 wind turbines and with a construction voltage of 36 kV. The simulations will be performed on a model for different system earthing alternatives to investigate the behavior of fault current and transient overvoltages during line-faults. Also, the simulations will investigate the impact of a lightning impulse. The simulation model is based on a specific wind farm and the software that will be used for the power system analysis is PSCAD/EMTDC. The result of the mapping indicates that the most common earthing method in Sweden is resonance earthing and for Europe, low-resistance earthing. In the simulations, it can be seen that the main difference between these two earthing methods is the fault current. The fault current is much greater for low-resistance earthing compared with resonance earthing. The simulation also indicates that the resonance earthed system causes the highest transient overvoltages compard with low-resistance earthing. The results of the lightning impulse simulations for resonance earthing shows that it is important to have a low value of the resistance of the earth electrode for a surge arrester to keep a lower voltage level.
Keywords: Elkraftteknik; Electric power engineering